Brexit giving shared sovereignty a bad name - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2016)
In a commentary, SMU Associate Professor of Law Eugene Tan shared his thoughts on Britain's vote to leave the European Union (EU). He noted that if the UK’s exit, or Brexit, is poorly managed, it may presage the slow decline and growing irrelevance of the EU in the global political economy. He opined that the tragedy of Brexit is the profound misunderstanding of sovereignty, adding the concern now is the risk of populist exit contagion gaining traction in other EU member states, all in the name of sovereignty and democratic choice. Associate Prof Tan also said the entire episode holds lessons for the Association of South-east Asian Nations (Asean). He pointed out that the abiding demand for and long-standing understanding of the sovereignty norm in Asean has resulted in a policy of non-interference and a consensual approach to decision-making. While this is pragmatic, the “Asean Way” has been criticised for its failure against recalcitrant member states, such as in Myanmar and the abuse of human rights there when it was under military rule. He concluded that sovereignty must galvanise the human desire to cooperate in enlightened self-interest for the greater good.